Proposta de modelo para apoio à realização do planejamento de médio prazo na construção civil - Angelim, Vanessa Lira (2019)
The medium-term level (MTL), which is a level of the Last Planner System of Production Control (LPS®), is essential to assure plans are executed as planned at the master (milestone) schedule level, is one of these levels. The objective of this work is to propose a model of improvement in the execution of medium-term planning in construction. The methodology adopted will be qualitative, using the Design Science Research strategy. Firstly, a phase of understanding about the subject was carried out through a systematic review of the literature and empirical studies. Next, the solution development phase was carried out by analyzing the difficulties and barriers in the MTL and the respective solution proposals that resulted in the formulation of a theoretical model. Finally, the evaluation of the model and explanation of learning and conclusions occurred. This work allowed to identify the main barriers and difficulties in the accomplishment of the MTL and which practices and strategies needed to solve the research problem. As a final result, this work proposed a theoretical process model for the MTL in construction. It can be concluded that involving all interested parties during the MTL, integrating the sectors of the company to collaborate for the shielding production process and systematizing and automating the accomplishment of the MTL is essential to reach the expected functions in its accomplishment.